Pengaruh Akupresur terhadap Fatigue pada Pasien Kanker yang Menjalani Kemoterapi - Ghozali, Imam; Allenidekania, Allenidekania; Waluyo, Agung; Gayatri, Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The study aims to explore the effectiveness of acupressure against fatigue in cancer patients undergoing chemotherapy. The method used is systematic review through the ProQuest, ScienceDirect, and Scopus databases. The results showed that from 6 articles studied showed that acupressure was effective in reducing fatigue in cancer patients undergoing chemotherapy. In conclusion, acupressure can reduce fatigue in induction chemotherapy. Key Word: Acupressure, Fatigue, Chemotherapy, Cancer Patients